2018
DOI: 10.1177/2373379918768329
|View full text |Cite
|
Sign up to set email alerts
|

Human Rabies Postexposure Prophylaxis Knowledge and Retention Among Health Professionals by Using an Online Continuing Education Module: Arizona, 2012 to 2015

Abstract: Health professionals have a need to continually maintain their competencies and a range of knowledge as new research, techniques, information, or ideas are exchanged or discovered. There are several barriers to obtaining required continuing education (CE), which can include the time spent and/or travel expenses incurred to participate in traditional CE courses (Garrison, Schardt, & Kochi, 2000). However, distance-based education, which refers to the formal method of study where students and instructors do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Despite the crucial importance of appropriate PEP for preventing death, baseline knowledge of rabies disease and its clinical management guidelines remains lacking or inadequate. 40 , 41 Appropriate initiation of PEP and correct administration of RIG are areas of deficiency for many healthcare providers. 40 Retrospective studies show low rates of adherence to treatment guidelines in the United States, with particularly high rates of incorrect omission of wound infiltration with RIG when indicated (i.e., when wound sites are present).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the crucial importance of appropriate PEP for preventing death, baseline knowledge of rabies disease and its clinical management guidelines remains lacking or inadequate. 40 , 41 Appropriate initiation of PEP and correct administration of RIG are areas of deficiency for many healthcare providers. 40 Retrospective studies show low rates of adherence to treatment guidelines in the United States, with particularly high rates of incorrect omission of wound infiltration with RIG when indicated (i.e., when wound sites are present).…”
Section: Discussionmentioning
confidence: 99%
“… 40 , 41 Appropriate initiation of PEP and correct administration of RIG are areas of deficiency for many healthcare providers. 40 Retrospective studies show low rates of adherence to treatment guidelines in the United States, with particularly high rates of incorrect omission of wound infiltration with RIG when indicated (i.e., when wound sites are present). Incorrect treatment in the form of insufficient or non-administration of RIG has been reported in 42% to 48% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases of fatal PEP treatment failure often occur secondary to guideline deviation with insufficient or omitted infiltration of wounds with RIG 5,6 . Despite changes in Centers for Disease Control and Prevention (CDC) Advisory Committee on Immunization Practices (ACIP) recommendations in 1999 to reflect a focus on wound infiltration with RIG, retrospective studies have revealed incomplete or omission of wound infiltration in nearly half of cases 7–9 …”
Section: Infiltration Of Rabies Immunoglobulinmentioning
confidence: 99%
“…Furthermore, ownership of RIG administration is inconsistent among institutions: wound infiltration is performed solely by providers at some institutions and by nurses at other facilities. Based on findings from an online continuing education module, health care workers in the United States demonstrated a particular knowledge gap on RIG, including its location of administration and role in providing passive immunity 9 . Unfamiliarity with immunoglobulins, vaccines, and their administration combined with a lack of granular guidance on wound infiltration technique creates a knowledge gap between evidence, guidelines, and the delivery of clinically appropriate, evidence‐based care for human rabies disease.…”
Section: Infiltration Of Rabies Immunoglobulinmentioning
confidence: 99%